2010
DOI: 10.1177/0748730410385281
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock Starts Ticking at a Developmentally Early Stage

Abstract: Although overt diurnal rhythms of behavior do not begin until well after birth, molecular studies suggest that the circadian clock may begin much earlier at a cellular level: mouse embryonic fibroblasts, for example, already possess robust clocks. By multiple criteria, we found no circadian clock present in mouse embryonic stem cells. Nevertheless, upon their differentiation into neurons, circadian gene expression was observed. In the first steps along the pathway from ES cells to neurons, a neural precursor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 40 publications
5
65
0
1
Order By: Relevance
“…This is in line with the emergence of circadian rhythmicity during differentiation of embryonic stem cells that do not possess a functional circadian clock 49, 53. Clock genes are expressed in ES cells, however, and the emergence of a functional clock system is closely linked to differentiation 49, 50, 51, 53, but these factors may have additional functions in those cells. The intimate link between clock proteins and the cell cycle was discussed above, and stem cell proliferation may be regulated by these factors.…”
Section: Future Perspectivessupporting
confidence: 63%
See 1 more Smart Citation
“…This is in line with the emergence of circadian rhythmicity during differentiation of embryonic stem cells that do not possess a functional circadian clock 49, 53. Clock genes are expressed in ES cells, however, and the emergence of a functional clock system is closely linked to differentiation 49, 50, 51, 53, but these factors may have additional functions in those cells. The intimate link between clock proteins and the cell cycle was discussed above, and stem cell proliferation may be regulated by these factors.…”
Section: Future Perspectivessupporting
confidence: 63%
“…In murine pluripotent stem cells, circadian rhythms were shown to be established when differentiation is induced upon withdrawal of leukemia inhibitor factor (LIF) (passive) or by the addition of retinoic acid (active) 49, 50, 51. When reversing differentiation through reprogramming 52, the clock is switched off again 49 (Fig 3A), which indicates that the (in)activation of the diurnal clock is a reversible process that is intensively linked with the differentiation state of a cell.…”
Section: The Circadian Clock In Stem Cell‐derived Cellsmentioning
confidence: 99%
“…In vitro, multiple laboratories have demonstrated that, whereas pluripotent embryonic stem (ES) cells show no visible rhythmicity, their differentiated counterparts -even multipotent neural precursor cells (NPCs) -show robust circadian oscillations of gene expression (Kowalska et al, 2010;Yagita et al, 2010). In elegant experiments, it was shown that these rhythms are lost upon de-differentiation of these cells back to ES cells, and regained upon re-differentiation to NPCs (Yagita et al, 2010).…”
Section: From Stem Cells To Developmentmentioning
confidence: 99%
“…By day 28, clear and robust rhythms were observed in D28 differentiated embryoid bodies (EBs) (Yagita et al 2010 ;Umemura et al 2013 ). The same holds true when stem cells are differentiated in a more directed way towards the neuronal lineage by addition of retinoic acid (Yagita et al 2010 ;Kowalska et al 2010 ). When differentiated cells are reprogrammed towards induced pluripotent stem cells (iPSCs), they lose their established oscillatory clock gene expression pattern.…”
Section: Oscillation Of Core Clock Genes Upon Differentiation Of Embrmentioning
confidence: 95%